Voices from the Civil War : a documentary history of the great American conflict - Meltzer, Milton, 1915-2009. (New York : Crowell, 1989)
Letters, diaries, memoirs, interviews, ballads, newspaper articles, and speeches depict life and events during the four years of the Civil War.
Includes index.
Bibliography: p. 195-198.
Keywords: United States -- History -- Civil War, 1861-1865 -- Sources -- Juvenile literature; United States -- History -- Civil War, 1861-1865.; United States -- Social life and customs -- 1783-1865.